Analysis of Beauty Table Laboratory Management in School High School - Puspitasari, Diah; Supraptono, Eko; Endroyo, Bambang (Journal of Vocational and Career Education, 2018)
Education plays an important role in improving the quality of the nation. The laboratory is the place for school learning. This research aims to analyze the management of laboratory and analyze the management of practice equipment and the completeness of practice equipment in SMK N Jawa Tengah. The benefit is that schools improve the quality of the laboratory. Methods in this study using qualitative methods. Informants from this research are teachers, students and laboran in the school. Data collection techniques in this study using observation techniques, interviews and documentation. Data analysis using triangulation analysis, increasing diligence to observe carefully, member check. Stage process in this research that is by researching laboratory management in School and management of practice equipment with attention to every aspect that is aspect of planning, organizing aspect, implementation aspect and supervision aspect. The results of the study generally do not meet the existing standards even though there are already schools that have Laboratory room that has adjusted the standards that are fed by the government, but not yet have good management, the School needs to improve the procurement of facilities and infrastructure equipment practice in the laboratory of beauty, the number of equipment practice, distribution of job desribtion in accordance with its ability, renovation of laboratory space, laboratory equipment laboratory, additional equipment for facials, new modern equipments added, comfort of practical room, addition of facial bed security of electrical installation, storage of practice equipment, laboratory personnel, supervision of cosmetics, supervision of member performance, supervision of activities in the laboratory of beauty.Â